Study of the thermal properties during the cyclic process of lithium ion power batteries using the electrochemical-thermal coupling model. (5th June 2018) - Tang, Yiwei; Wu, Lijue; Wei, Weifeng; Wen, Dingqiang; Guo, Quanwen; Liang, Weichun; Xiao, Li
Highlights: An electrochemical-thermal capacity fade model is developed. The solvent reduction reaction is considered. Every part heat generation and evolutions are analyzed. The evolution of heat generation with cycle index is discussed. Abstract: In this work, a soft pack (20 Ah LiFePO4 /MCMB) lithium ion battery is used as a prototype to develop a mathematical model and carry out a numerical simulation of the thermal properties associated with the cyclic process of a lithium ion power battery. This model incorporates the solvent reduction reaction on the anode, which is thought to be a dominant aging mechanism. Capacity fade is based on the loss of active lithium ions due to solvent reduction reaction on the anode and on the rise of anode film. The variation of internal ohmic heat, electrochemical reaction heat, and polarization heat of the battery during the constant-current discharge and constant-current and constant-voltage charge, as well as its relationship with capacity fading during the cyclic process are analyzed quantitatively. The results show that when a lithium ion battery is charging and discharging at a conventional rate, polarization and electrochemical reactions are the main causes for heat production. Capacity fading during the charging and discharge process affects both the charging and discharging time of the battery. It also affects the charging state of the electrode at a certain moment of charging or discharging, which changes the thermal behavior of the battery.